1984
DOI: 10.1203/00006450-198406000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxanthine and Oxygen Induced Lung Injury: A Possible Basic Mechanism of Tissue Damage?

Abstract: Summaryoxygen exposure with simultaneous intravenous hypoxanthine infusion. Lung injury was induced in young rats by a continuous infusion of hypoxanthine intravenously and breathing 100% oxygen for 48 h (group 1). Control animals were rats infused glucose and MATERIALS AND METHODSbreathing 100% oxygen (group 2), rats infused hypoxanthine in room air (group 3), and untreated rats (group 4). In group 1 rats interstitial and alveolar edema was found with a tendency toward marked margination of polymorphonuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…A series of experimental studies have shown that the free radical-generating system, hypoxanthine-xanthine oxidase, can damage the lung [7,[21][22][23]. These experimental data are supported by the results of Russell and Cooke [24] showing that premature infants who subsequently developed CLD had higher plasma hypoxanthine levels at birth than those who did not develop CLD.…”
Section: Effect Of Increased Oxidative Load On the Lungsupporting
confidence: 76%
See 1 more Smart Citation
“…A series of experimental studies have shown that the free radical-generating system, hypoxanthine-xanthine oxidase, can damage the lung [7,[21][22][23]. These experimental data are supported by the results of Russell and Cooke [24] showing that premature infants who subsequently developed CLD had higher plasma hypoxanthine levels at birth than those who did not develop CLD.…”
Section: Effect Of Increased Oxidative Load On the Lungsupporting
confidence: 76%
“…A new momentum in the search for the pathogenetic mechanism(s) of this condition occurred, however, when the hypothesis was introduced that oxygen free radicals may play a significant role in its development [6,7], and further that CLD is only one facet of the so-called oxygen radical disease of the newborn infant [8]. This new concept has made it clear that hyperoxia is only one possible factor contributing to oxidative stress.…”
mentioning
confidence: 99%
“…To test this hypothesis we performed an experiment in which young rats were infused intravenously with hypoxanthine while breathing 100% oxygen for 48 h. Compared with control animals breathing 100% oxygen and infused with glucose, or animals infused with hypoxanthine but breathing room air, we found hemorrhage and edema in the lungs (105). In lung lavage there was a many-fold increase in protein content.…”
Section: Hypoxanthine As An Oxygen Radical Generatormentioning
confidence: 99%
“…Oxygen-derived free radicals play an important role in experimentally induced hypoxic-reoxygenation injury (4,5), and may be responsible for both hypoxic and hyperoxic aspects of pulmonary damage (6)(7)(8). One source of oxidant genertion in the lungs may be the Hx-XO system (6).…”
mentioning
confidence: 99%